2021
DOI: 10.32890/mjli2021.18.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Instructor Feedback, Self-Regulation, Assignment Completion and Academic Achievement in Thai Higher Learning Institutions

Abstract: Purpose – Aassignments have been linked with various benefits, including a higher quality of learning and academic achievement. The purpose of this study was to explore the relationship between assignment completion and academic achievement in higher education. Specifically, it investigated the impact of instructor feedback and three constructs of self-regulation (self-efficacy, time management, and help-seeking) on assignment completion (time spent on assignments and number of assignments completed) and acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
1
9
0
3
Order By: Relevance
“…In the most recent research by Ozer and Akcayoglu (2021), anxiety was found to play a vital role in students' academic performance with self-regulation being a strong predictor of class attendance, resulting in successful foreign language learning. Suamuang et al (2021) also revealed a relationship between the components of self-regulation and students' academic achievement. However, the results demonstrate the prominence of self-regulation in the learning process only in the context of higher learning institutions, especially in Thailand.…”
Section: Discussionmentioning
confidence: 87%
“…In the most recent research by Ozer and Akcayoglu (2021), anxiety was found to play a vital role in students' academic performance with self-regulation being a strong predictor of class attendance, resulting in successful foreign language learning. Suamuang et al (2021) also revealed a relationship between the components of self-regulation and students' academic achievement. However, the results demonstrate the prominence of self-regulation in the learning process only in the context of higher learning institutions, especially in Thailand.…”
Section: Discussionmentioning
confidence: 87%
“…Assignment log was adapted from Bembenutty and White [11]. In the current study, assignment log was designed on the google drive of students' university accounts.…”
Section: Assignment Logmentioning
confidence: 99%
“…Students will report their assignment activities weekly regarding all kinds of assignments, both in and outclass via their google drive. An assignment log or learning log is a key material for monitoring and tracking students' assignment practices [11,20]. It represents a journal of students' learning, which encourages students to perceive their weak and strong skills and connect to prior personal learning backgrounds [20].…”
Section: Assignment Logmentioning
confidence: 99%
See 2 more Smart Citations